Rehab-Immersive: A framework to support the development of virtual reality applications in upper limb rehabilitation - Vanesa Herrera; David Vallejo; José J. Castro-Schez; Dorothy N. Monekosso; Ana de los Reyes; Carlos Glez-Morcillo; Javier Albusac (SoftwareX, 2023)
In this article, we present a framework, called Rehab-Immersive (RI), for the development of virtual reality clinical applications as a complement to the rehabilitation of patients with spinal cord injuries. RI addresses the interaction of patients with virtual worlds, considering upper limb motor impairments. A preconfiguration allows customization for each patient’s specific needs. RI also stores kinematics data, providing clinical staff with a valuable tool to evaluate progress and patient exercise performance. As an example, a virtual version of the Box & Block test is presented.